Branding Regenerative Tourism for Sustainable Rural Destinations : A Critical Reflection Perspective - Shankar Ravichandran, Sabari (Indian Journal of Marketing, 2023)
Purpose : Regenerative tourism is widely popular in many countries. With the changing dynamics of tourists across the globe, disruptive challenges in managing the destinations and uncertainties in delivering tourism offerings have clouted the significance of regenerative toruism mainly catering to rural destinations. The crux of this critical reflection perspective (CRP) was to infer more on the sustainability perspectives through regenerative tourism and to reflect on the avenues of branding regenerative tourism for a sustainable future of rural destinations. Methodology : This CRP is based on the self-reflection of the author based on the readings from literary sources, exposure to research outcomes, and experience in consulting destination management organizations. Hence, a mixed method of reflection exercise has been performed on the acquired content over the years. Findings : As novel findings, this CRP infers on the imposition of a regenerative tourism image with the notion of sustainability of rural destinations. Also, the relevance of food tourism, creative tourism, and agri tourism referring to regenerative tourism for the sustainable future of rural destinations have been inferred. Practical Implications : Careful strategic branding framework on building regenerative tourism with the elements of food, creative, and agri tourism will eventually attract wide segments of tourists across the globe, perhaps contributing more towards the sustainable future of rural destinations. Social Implications : This CRP highlights the benefits of regenerative tourism for sustainable consumption of tourism resources that would handover the valuable tourism resources to the next generations without degrading their originality. Limitations/Scope : The inferences derived are solely based on the competence of the author’s opinions. The research avenues highlighted here, if performed with suitable robust methodology, will produce valuable insights into literature and facilitate in conceiving novel contexts in tourism marketing. Originality/Value : This CRP is based on an evolving concept in developed and developing countries and highlights the novel perspectives of blending regenerative tourism with food tourism, creative tourism, and agri tourism with reference to the marketing communication elements. These perspectives haven’t been attempted in the given literary sources and are highly aligned with the tourism industry’s current state-of-the-art trends.